Improving parental engagement for disadvantaged students - Sargent, D (2020)
Engaging the parents of secondary school students in the educational lives of these young people is a major challenge for most secondary schools. The objectives of this action research project were to: explore the specific types of parental engagement that can be beneficial to learners, to investigate the extent to which students in school A experience the types of parental engagement that have been identified as beneficial, and ascertain whether promoting parental engagement is an effective way to better engage students and parents in education. This project sought to explore these aspects with the families of disadvantaged students, specifically. Whilst data collection was significantly limited by the coronavirus pandemic of 2020, partial data allowed for the tentative conclusions that a robust relationship between school staff, parents, and students is crucial in supporting students engage more readily in school and that this relationship is best promoted by high-quality and regular communication between school staff and the parents of disadvantaged students.